Extensive Bilateral Extraluminal Perivascular Pulmonary Haemorrhage Associated with Stanford Type A Aortic Dissection - Angeline Reid; Peter Stride; Jonathan Hunter; Katerina Liew; T. Wood; Mostafa Seleem (Case Reports in Medicine)
We present the case of an 80-year old man with a Stanford Type A dissecting thoracic aortic aneurysm plus the unusual CT finding of extramural haemorrhage along the pulmonary vessels. The clinical and radiological picture has an extremely high mortality